The Design of Systems for Learning and Working in Librarianship - Birchall, Alex; Rada, Roy (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The paper presents a philosophy and theory for the design of a system that would mediate between the librarian as a knowledge worker and the library as a learning organization. It does this by combining Activity Theory and Ecological Interface Design.. The task to be supported is that of classification. The hypothesis is that the task of library classification can be supported by using the surrounding organization as an interactive learning environment, as the process of organizational learning depends on an appreciation of the cognitive process of classification.